Pulse Pressure Variation Patterns in a Swine Model of Hypovolemia under Spontaneous Breathing vs. Invasive Positive-Pressure Ventilation - Rocha,Mauricio Macário (2014)
OBJECTIVE: This study was performed to obtain the title of Master in Medicine, Nov/2012-Jul/2013. Improvement in cardiac output after fluid administration is known as fluid responsiveness. A reliable parameter for its evaluation is pulse pressure variation: it has established its utility in predicting volume responsiveness in mechanically ventilated patients. METHOD: Pulse pressure variation was analyzed in 10 anesthetized male pigs at four different stages: I) normovolemia and spontaneous breathing; II) hypovolemia and spontaneous breathing; III) hypovolemia under mechanical ventilation; and IV) after volume replacement, under mechanical ventilation. Cardiac output, pulmonary artery occlusion pressure, systolic pressure variation, mean arterial pressure, and heart rate were measured at all stages; red blood cell count was determined at stages I, II, and IV. RESULTS: Mean pulse pressure variation values during hypovolemia with spontaneous breathing (stage II) were significantly higher than at any other stage. After institution of mechanical ventilation, pulse pressure variation values returned to baseline without fluid administration. The lowest values were achieved after volume replacement. CONCLUSION: Pulse pressure variation values are higher during spontaneous breathing than during mechanical ventilation. Thus, it may be useful for assessment of fluid volume under these conditions, with baseline values as a starting point to which serial measurements should be compared after institution of specific therapy.